Contribution of non-work and work-related risk factors to the association between income and mental disorders in a working population: the Health 2000 Study. Issue 3 (18th February 2008) - Virtanen, M; Koskinen, S; Kivimäki, M; Honkonen, T; Vahtera, J; Ahola, K; Lönnqvist, J
Abstract : Objectives: To examine the contribution of non-work and work factors to the association between income and DSM-IV depressive and anxiety disorders in a working population. Methods: A representative sample of the Finnish working population aged 30–64 (1667 men, 1707 women) in 2000–2001 responded to a survey questionnaire on non-work factors (marital status, housing conditions, non-work social support, violence victimisation, smoking, physical symptoms), work factors (job demands, job control, social support at work, educational prospects, job insecurity) and household income. Somatic health was examined in a standard health examination. The 12-month prevalence of depressive and anxiety disorders was examined with the Composite International Diagnostic Interview. Results: The risk of having a depressive or anxiety disorder was 2.8 times higher in the low-income group than in the high-income group among men and 2.0 times higher among women. For men, non-work and work factors explained 20% and 31% of this association, respectively. For women, the corresponding figures were 65% and 23%. Conclusions: Low income is associated with frequent mental disorders among a working population. In particular, work factors among men and non-work factors among women contribute to the income differences in mental health.